Carl R. Rogers (1902-1987): Friend, Gentleman, and Scholar - Van Hesteren, Frank (Canadian Journal of Counselling and Psychotherapy, 2011)
This article is written in memory of Carl R. Rogers. An attempt is made to convey a sense of the spirit of Rogers' thinking and of the kind of person he was, both in his own eyes and in the experience of those who knew him personally. The article is concluded with a discussion of how Rogers' "way of being" has influenced the writer's own personal and professional development.